Degree of possession of teachers of Islamic education for the professional qualifications of secondary school students from the point of view of school principals in Mafraq Governorate - Rqabat, Raed Mohammed Mfdi (Journal of Educational and Psychological Sciences, 2018)
The study aimed at revealing the degree to which the teachers of Islamic education for the professional competencies in teaching Islamic education to secondary school students from the point of view of school principals in Mafraq governorate. To achieve the objectives of the study, the researcher used the descriptive approach. He constructed a study tool consisting of (20) A random sample of 325 managers and managers was selected. The results indicated that the degree to which the teachers of Islamic education in the field of vocational education from the point of view of the principals of the public schools in Mafraq Governorate was high (3.86). The order of the fields was ranked in descending order according to the competency level: , The efficiency of the teaching, average (4.02), the efficiency of the calendar, average (3.76), the planning skills, average (3.55). The results also showed that there are no statistically significant differences at the level of (α = 0.05) In teaching Islamic education to high school students The point of view of school principals in Mafraq Governorate due to the variable sex. In the light of the results, a number of recommendations and proposals were presented to increase the degree of ownership of vocational education by teachers of Islamic education in the schools of Mafraq Governorate and the whole of the Kingdom of Jordan.
Keywords: professional competencies; school principals; public schools; Mafraq Governorate